(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigated the feasibility of reducing energy demand in residential buildings using a new material called “Phase Change Material with Mycelium Integration (PCMMI)”, considering the climatic conditions in Jordan, Amman. A parametric analysis was conducted to calculate the time-lag of the materials in the components of the residential envelope. The parametric analysis was applied to estimate the duration which the residential building is exposed to solar heat. The results showed that the average of the delay is about 8 hours. Which means that if the temperature outdoor is 30 oC it will take the envelope 8 hours to radiate it to the interior’s peak temperature after adding the PCMMI layer to the layers of the envelope.